2001
DOI: 10.1034/j.1399-3011.2001.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic peptides from the N‐domains of CEACAMs activate neutrophils

Abstract: Four members of the carcinoembryonic antigen family, CEACAM1, CEACAM8, CEACAM6 and CEACAM3, recognized by CD66a, CD66b, CD66c and CD66d monoclonal antibodies (mAb), respectively, are expressed on human neutrophils. CD66a, CD66b, CD66c and CD66d mAb binding to neutrophils triggers an activation signal that regulates the adhesive activity of CD11/CD18, resulting in an increase in neutrophil adhesion to human umbilical vein endothelial cells. Molecular modeling of CEACAM1 using IgG and CD4 as models has been perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 82 publications
0
18
0
Order By: Relevance
“…Despite absence of a transmembrane domain, GPI-linked proteins such as CEACAM6 are capable of transducing transmembrane signals. In the neutrophil, specific antibody-mediated crosslinking of CEACAM6 induces neutrophil activation (Robinson and Hederer, 1994;Skubitz et al, 2001). Although lacking a proteinaceous intracellular domain, colocalization experiments indicate that GPI-linked proteins such as CEACAM6 may be able to influence intracellular events by modulating second messengers and src-family tyrosine kinases in lipid rafts via their GPI anchor (Brown, 1993;Malek et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite absence of a transmembrane domain, GPI-linked proteins such as CEACAM6 are capable of transducing transmembrane signals. In the neutrophil, specific antibody-mediated crosslinking of CEACAM6 induces neutrophil activation (Robinson and Hederer, 1994;Skubitz et al, 2001). Although lacking a proteinaceous intracellular domain, colocalization experiments indicate that GPI-linked proteins such as CEACAM6 may be able to influence intracellular events by modulating second messengers and src-family tyrosine kinases in lipid rafts via their GPI anchor (Brown, 1993;Malek et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…CEACAM6 is normally expressed by granulocytes (Skubitz et al, 2001), but is overexpressed in various human cancers (Cournoyer et al, 1988;Thompson et al, 1991;Scholzel et al, 2000;Gardner-Thorpe et al, 2002). In colorectal carcinoma, CEACAM6 levels correlate inversely with cellular differentiation (Ilantzis et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, we cannot exclude the involvement of homophilic interactions between CEACAM1 molecules on leukocytes and blood or lymphatic endothelium, leading to extravasation or close endothelial interaction and subsequent incorporation into the vasculature, because CEACAM1-derived peptides enhance adhesion of neutrophilic granulocytes to immobilized human endothelial cells. 40 Furthermore, it is not known if CEACAM1-mediated adhesion influences autocrine or juxtacrine signaling processes during inflammation or whether high cellular densities are required to create an angiogenic milieu. We have previously described that CEACAM1 is implicated in hemangiogenesis and vascular remodeling and that CEACAM1 expression enhances tissue recovery and capillary formation after femoral artery ligation.…”
Section: Discussionmentioning
confidence: 99%
“…Three peptides from the N-domain of CEACAM1, and one homologous CEACAM5 peptide, activated neutrophils as determined by increasing neutrophil adhesion to HUVEC monolayers. 36,37 CEACAM5, also known as CEA, is expressed by many carcinomas and was the first tumor marker to be used in clinical practice. It was concluded that at least three peptide motifs from the N-terminal domain of CEA-CAM1 were involved in the interaction of CEACAM1 with other ligands, and can initiate signal transduction in neutrophils.…”
Section: Introductionmentioning
confidence: 99%